(untitled) (TEST BioLaw Journal - Rivista di BioDiritto, 2025)
CPR, as places of detention, have a heavy impact on mental health of people imprisoned. The only crime committed by these people is to escaped from wars and persecutions to survives, or to look for a better life, exposing themselves to potentially traumatic experiences. They are locked up in non-places made specifically to lose identity and adhere to that offered by the total Institution. As Augè and Goffman remind us, cultural, psychological and anthropological contexts modify the person in their behavior and also in their perception of themselves and others, making them even more vulnerable to various mental disorders